An investigation into the erroneous access and egress behaviours of building users and their impact upon building performance. Issue 9 (27th April 2020) - Dixon, Charlotte; Edwards, David John; Mateo-Garcia, Monica; Lai, Joseph; Thwala, Wellington Didibhuku Didibhuku; Shelbourn, Mark
Abstract : Purpose: This study aims to investigate the behaviour of building users and how this impacts upon building energy performance. Specifically, the work examines the behavioural traits of able-bodied users of a large higher education building who erroneously access and egress the building using doorways intended for disabled users. Design/methodology/approach: An inductive methodological approach is adopted that uses grounded theory to devise new insights into building users' access and egress habits. Structured interviews are conducted to collect primary data from 68 building users of a large educational building over a four-week period. Responses to questions posed provide the basis for a tabularisation of behavioural traits. Findings: Reasons for able-bodied building users' preferences to using disabled access are identified and discussed; these are thematically grouped under the headings of apathy, convenience, emergency, ergonomics, ignorance and phobia. Building upon these findings, the research then offers insights into the approaches that could be adopted to change the erroneous behaviours. These approaches include education of building users on the impact their behaviour has upon building performance and environmental pollution, more stringent regulation to penalise repeat offenders and changes to building entrance design using obtrusive (i.e. radio frequency identification tags) and unobstrusive control measures (i.e. a second entrance doorway or slower opening mechanism). Originality/value: To the best of the author's knowledge, this study is the first of its kind to investigate the rationale for able-bodied building users erroneously using disabled persons' access and egress doorways within a building, which as a consequence, inadvertently reduces the building's environmental performance.